Religiusitas Gunung Merapi - Eko Punto Hendro (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
The concept of 'manunggaling kawula gusti', which had developed in Java in ancient times, until now still colored the behavior of people living around Mount Merapi, which among others demanded the full devotion of the people to the Sultan and his magical companions, namely Baurekso Mount Merapi and Nyi Rara Kidul in the southern sea. Mbah Marijan and some of her descendants and followers still show loyalty, so in order to keep their Merapi they offer to the Sultan as the ruler of the human world, which is often regarded as the incarnation of Gods / Lords of the rulers of the universe. In this way they believed that their spirits would later merge with Gusti as their worship, as a form of uniting the people's physical body to the king and to rule over nature. The purpose of this study is to find out more about the meanings contained in Mount Merapi, namely the mountain that is feared and sacred by the people of Yogyakarta, and especially those who live on the slopes of Merapi.